Awake Fiberoptic Intubation for a Giant Multinodular Struma Presenting with Acute Respiratory Failure: A Case Report - Abdulrahman Rizky Sulajman; Jeffri Prasetyo Utomo; Buyung Hartiyo Laksono (Open Access Indonesian Journal of Medical Reviews, 2025)
A giant multinodular struma can cause severe upper airway obstruction, presenting a formidable challenge to anesthesiologists and emergency physicians. Securing the airway is a priority, yet conventional intubation methods carry a high risk of failure and complete airway collapse. Awake Tracheal Intubation (ATI) is a critical technique for managing these anticipated difficult airways, allowing for the maintenance of spontaneous respiration while securing a definitive airway. This report details the emergency management of a patient with near-fatal airway compromise due to a massive goiter. A 51-year-old female presented to the emergency department with severe dyspnea that had worsened over three days. She had a 20-year history of a progressively enlarging neck mass, which was now of a massive size. The patient exhibited signs of acute respiratory failure, including stridor, subcostal retractions, a respiratory rate of 30 breaths/minute, and a decreased level of consciousness. Imaging confirmed a large soft tissue mass causing significant tracheal narrowing from the C4 to C6 vertebral levels. Given the impending airway collapse, an emergency awake fiberoptic intubation was performed. With minimal sedation and continuous oxygenation, a size 6.0 endotracheal tube was successfully placed into the trachea under direct bronchoscopic guidance. The patient’s oxygenation and ventilation improved immediately post-procedure. In conclusion, this case underscores the lifesaving potential of awake fiberoptic intubation in patients with a critically compromised airway from a giant multinodular struma. The ability to maintain spontaneous breathing and provide continuous oxygenation during the procedure is paramount in preventing catastrophic outcomes. This technique should be a core competency for clinicians managing difficult airways in the emergency setting.